Unobserved heterogeneity in the determinants of under-five mortality in Nigeria: Frailty modeling in survival analysis (2019)
Childhood mortality is one of the measure of socio-economic status of a population. Several studies have been conducted to identify determinants of childhood mortality but the random effect and heterogeneity nature in most clustered survey data has not been well documented. The present study was designed to use shared frailty model to assess determinants of Under-Five Mortality (U5M) using an hierarchical data in Nigeria.